Tabattul di Era Digital: Analisis Hukum Islam atas Fenomena Hidup Membujang di Palembang - M. Riko Ripardo; Rafida Ramelan (CV. Doki Course and Training, 2025)
Marriage in Islam is considered a strong covenant (mitsaqan ghalizan). The intense exposure to social media has influenced individuals’ perspectives on marriage, values, and expectations. This trend has led many young people to delay or even decide not to marry at all. The phenomenon of remaining single (tabattul) is particularly evident in Bukit Baru Subdistrict, Ilir Barat 1, Palembang, where a number of young adults of marriageable age choose to remain unmarried. This study aims to identify the factors causing tabattul due to social media and to analyze them from the perspective of Islamic law. This field research employs a qualitative approach, using both primary and secondary data obtained through observation, interviews, and documentation, then analyzed descriptively. The findings show that the main factors behind tabattul influenced by social media are the desire to maintain personal freedom and focus on a career, in addition to the influence of cases of domestic violence, family conflicts, patriarchal partners, and partners who practice silent treatment. Moreover, some respondents choose tabattul based on religious motivation, such as devoting themselves to worship and seeking knowledge, following the example of earlier scholars. From the perspective of Islamic law, pursuing a career and personal freedom is not prohibited; however, refusing marriage solely due to fears shaped by social media is not justified. Marriage is still regarded as the primary path to preserving honor, avoiding harm, and attaining blessings through a family built upon sakinah, mawaddah, and rahmah